Reproductive biology of the European anchovy Engraulis encrasicolus (Linnaeus, 1758) in the Turkish Aegean Sea - Taylan Burcu; Bayhan Bahar (Oceanological and Hydrobiological Studies)
The present study investigated the reproductive biology of European anchovies obtained seasonally from fishermen in İzmir Bay (Aegean Sea). The total length range of the investigated individuals was 9.0 – 15.7 cm. Of the 750 samples in which sex was determined, 34% were males, and 66% were females, resulting in a female-to-male ratio of 1.91:1. The first maturation length was determined to be 10.47 cm for females and 9.95 cm for males. Based on the total values of the gonadosomatic index, it was concluded that the reproductive period of the species falls in the summer season. The batch fecundity of the species ranged from 2.123 to 6.951 oocytes, and the fecundity–length relationship was expressed as F = 1134.4TL – 10034 (R2 = 0.84). Histological examination of the female ovaries revealed the presence of oocytes at different stages of development, indicating multiple spawning during the reproductive season.